Forum ekspertówExtra-contractual health care services - Kubot, Zdzisław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Professor Zdzis³aw Kubot is a distinguished Wroc³aw lawyer and a co-initiator of innovatory legal solutions for the 1989 health service reform in Poland. In his article, he indicates various legal, and indirectly also medical and economic, aspects of extra-contractual services provided by health care centres in Poland in 2010. The views expressed in the article “Extra-contractual health care services in Poland” (“Pozakontraktowe œwiadczenia opieki zdrowotnej w Polsce”), published with the consent of the Author and the Editors of “Law and Medicine” (“Prawo i Medycyna”), can be summarised as follows: 1. Extra-contractual health care services do not constitute a homogeneous category but encompass over-limit services (provided to the insured as part of general health insurance) and commercial services. 2. Within the over-limit category, there are services provided as a statutory duty, i.e. based on Article 7 of the Health Care Centres Act, Article 30 of the Act on Medical and Dental Professions, Article 19 of the Act on Health Care Services Financed from Public Funds, and services provided outside the statutory duty. 3. Health care services provided as part of the statutory duty are divided into services financed by the National Health Fund (NHF) and services not covered by this payer. 4. Extra-contractual health care services not paid by the NHF or from the state budget are services whose costs are covered from the health care provider’s own budget. The services are not homogeneous in their legal character. There are services for which the service provider makes a claim to recover funds from the NHF and services for which no such claim against the NHF is made. 5. Extra-contractual health care services provided to the insured and financed from the health care provider’s own funds are a very specific type of services. Such services are not stipulated in the system of general health care insurance. They are of an insurance character because of the individuals to whom such services are provided; however, they are not financed from the systemic payer’s funds. 6. The interpretation that a public hospital, an NHF contracting party, cannot gain an income – on the basis of civil-law agreements – from the sale of health care services to insured individuals, should be rejected. Public hospitals cannot be denied the possibility to develop commercial services. 7. The provision of commercial medical services by public hospitals is subject to various limitations but is generally not precluded [27]. 8. Commercial medical services may be provided to insured individuals outside medical health care services financed from public means. The contract ability of an independent public health care centre with regard to hospital treatment is not of a sectional character, limited to contracts stipulated in the Act on Provision of Health Care Services Financed from Public Funds. 9. A public hospital cannot enter into civil-law agreements for hospital treatment which is covered by an NHF contract or for the treatment of patients executed as a statutory duty. Generally, a public health care centre cannot enter into civil-law agreements for hospital treatment if such treatment is covered by public finances. 10. Commercial services provided by public hospitals outside health care services financed from public funds do not change the status of the public health care centre as a non-profit entity with regard to health care services. 11. Allowing public hospitals to provide commercial medical services has an impact on the categorisation of extra-contractual health services provided by such hospitals. Extra-contractual services can no longer be qualified exclusively as services provided to insured individuals and which should be financed from public funds. 12. Allowing public hospitals to provide commercial medical services outside the services financed from public funds will limit the scale of disagreements between hospitals and the NHF with regard to over-limit health services. 13. Allowing public hospitals to provide commercial medical services eliminates the unfavourable (to such hospitals) state of loss of benefits ensuing from such services. 14. Extra-contractual health care services require investigations with regard to private law, tax law and accountancy regulations. The legal basis and the group of over-limit services should be investigated according to civil law and general health insurance law, which constitutes a part of social insurance law. Separate investigations should be carried out with regard to commercial services financed by patients, and services launched by insurance companies. 15. Health services financed by service providers themselves should be the subject of private-law and tax analysis. It is a particular category of health services whose provision does not result in a payment claim against the patients or against the NHF. 16. With regard to commercial medical services provided by private hospitals, it is essential to determine the relation between such services and health care services covered by a contract between the service provider and the NHF; it is also necessary to establish the prices of commercial and non-commercial services. 17. The variety of extra-contractual health care services implies the creation of a multi-segment health care system in Poland [28]. The introduction of further segments into the health care system is justified. The changes should evolve towards a closer relationship be-tween the method of financing and the type of “non-health” risk. Funds should be identified appropriately to the character and the multi-section organisation of health care [29].